Retraction Notice to"Intercultural Learning Supported by Technology: A Small-Scale Systematic Review" [International Journal of Education and Learning 1(1) (2019) 33-41] - Wayan Sintawati (International Journal of Education and Learning, 2019)
Following a rigorous, carefully concerns and considered review of the article published in International Journal of Education and Learning to article entitled “Intercultural Learning Supported by Technology: A Small-Scale Systematic Review" [International Journal of Education and Learning Vol 1, No 1, 2019, 33-41], DOI: http://dx.doi.org/10.31763/ijele.v1i1.30. This paper has been found to be in violation of the International Journal of Education and Learning Publication principles and has been retracted. This article has been retracted at the request of the Supervisor, Rustam Shadiev (Nanjing Normal University, China), of the author, Wayan Sintawati (Nanjing Normal University, China), because the author didn't communicate with him to publish the research work in this journal and didn't write his name on the article as responsible to teamwork effort. This practice is count as the unethical publication of the International Journal of Education and Learning.